2008 16th IEEE International Conference on Program Comprehension 2008
DOI: 10.1109/icpc.2008.15
|View full text |Cite
|
Sign up to set email alerts
|

Do Dynamic Object Process Graphs Support Program Understanding? - A Controlled Experiment.

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…The solutions given by the Ecl+Ext subjects were 43.38% more accurate (Table IV), averaging 17.88 out of 24 points compared to 12.47 points for the Eclipse group. 9 Related studies point out that it is not uncommon for several tasks to remain unfinished during the actual experiments (e.g., [48] and [40]). Similar to the timing data, the requirements for the use of the parametric t-test were met.…”
Section: B Correctness Resultsmentioning
confidence: 99%
“…The solutions given by the Ecl+Ext subjects were 43.38% more accurate (Table IV), averaging 17.88 out of 24 points compared to 12.47 points for the Eclipse group. 9 Related studies point out that it is not uncommon for several tasks to remain unfinished during the actual experiments (e.g., [48] and [40]). Similar to the timing data, the requirements for the use of the parametric t-test were met.…”
Section: B Correctness Resultsmentioning
confidence: 99%
“…Other researchers also conducted controlled experiments to validate tools supporting software maintenance tasks: Cornelissen et al [5] evaluated a trace visualizing tool with 24 student subjects. Quante et al [18] evaluated with 25 students the benefits of Dynamic Object Process Graphs (DOPGs) for program comprehension.…”
Section: Related Workmentioning
confidence: 99%
“…Include more than one subject system in the experimental design. The experiment of Quante [Qua08] showed that performing the same experiment on two different systems can lead to significantly different results. Therefore, in our experiment, we consider two systems, different in both scale and application domain.…”
Section: Wish List Extracted From the Literaturementioning
confidence: 99%
“…In spite of the increased complexity in organizing the experiment and analyzing the data, introduced by a second independent variable, we chose to perform the experiment with two different object systems. Besides our interest in analyzing the effect of the object system size on the performance of CodeCity's users, we also applied the lessons learned from Quante's experiment [Qua08] that the results obtained on a single object system are not reliable. The two object systems we opted for are well-known open-source systems of different, realistic sizes (see Table 7.2) and of orthogonal application domains.…”
Section: External Validitymentioning
confidence: 99%
See 1 more Smart Citation